PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN UNTUK MENENTUKAN IDE POKOK PARAGRAF DENGAN MENGGUNAKAN METODE INQUIRY BAGI SISWA KELAS VII B SMP NEGERI 7 SIGI - Roong, Jenni Dina (BAHASANTODEA, 2015)
This research aims at describing the process of applying Inquiry Method to increaseReading Comprehension ability in determining main idea of the VIIB grade students of SMP Negeri 7 Sigi. The research was designed as Classroom Action Research which was carried out in two cycles. The subject of the research was the VIIB grade students which consist of 32 students. The result showed that there was the increasing of students’ activities and learning outcome from cycle I to cycle II. The increasing can be proved by the result of analyzing students’ activities in cycle I on the first meeting was 55,88% and the second meeting was 75,00%, in cycle II, the result was 94,11%. The classical achievement of learning outcome in cycle I was 56,25% and classical absorbing was 68,28%, in cycle II classical achievement was 93,75% and classical absorbing was 87,03%, the criteria of comprehension concept was in very good category. Based on the result of research, it can be concluded that the implementation of Inquiry Method can increase the VIIB grade students’ activities and learning outcomein determining main idea. Keywords: Inquiry Method, Activities, Learning Outcome